Proceedings of the 41st International Academic Conference, Venice 2018
DOI: 10.20472/iac.2018.041.020
|View full text |Cite
|
Sign up to set email alerts
|

Green Building Public Awareness for Client`s Benefits Realization in Kano, Nigerian

Abstract: Despite all the global stakeholders call for a paradigm shift from the traditional design and construction practices, green buildings awareness for greater client`s benefits realization is still lagging in the Nigerian construction industry. It is premise that, lack of adequate client awareness on the potential benefits realization and high costs associated with design and construction are seen to be key barriers in delivering green and sustainable buildings in the construction industry. Viewed from the concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 1 publication
(1 reference statement)
2
2
0
Order By: Relevance
“…The study also suggested through the effect size computation that these factors could cause the differences to have a large effect (r = 0.843). This result supports that of Komolafe and Oyewole (2018) and Ibrahim and Raji (2018) who found a low level of awareness of the benefits of sustainable construction among building users and clients (non-professionals), respectively. It also aligned with such studies as Ifije and Aigbavboa (2020), Nduka and Sotunbo (2014) that recognised the increasing awareness level among construction stakeholders.…”
Section: Baltic Journal Of Real Estate Economics and Construction Man...supporting
confidence: 87%
See 3 more Smart Citations
“…The study also suggested through the effect size computation that these factors could cause the differences to have a large effect (r = 0.843). This result supports that of Komolafe and Oyewole (2018) and Ibrahim and Raji (2018) who found a low level of awareness of the benefits of sustainable construction among building users and clients (non-professionals), respectively. It also aligned with such studies as Ifije and Aigbavboa (2020), Nduka and Sotunbo (2014) that recognised the increasing awareness level among construction stakeholders.…”
Section: Baltic Journal Of Real Estate Economics and Construction Man...supporting
confidence: 87%
“…The study also suggested that in the event of unavailability or difficulty in application of those strategies with a high importance level, alternative strategies with a medium-high importance level could be adopted. This also supported the positions Ganganaboina and Raiz (2017), Ibrahim and Raji (2018), Oluwole (2017), Sunthonkanokpong and Murphy (2019).…”
Section: Baltic Journal Of Real Estate Economics and Construction Man...supporting
confidence: 74%
See 2 more Smart Citations